Integrasi Agama dan Budaya pada Masyarakat Kutai (Model Peacebuilding Interreligius dan Interkultural) - Khojir Khojir; Dian Wahid Hermawan; Sulthon Fatoni (Al-Ulum, 2018)
Religious and cultural peacebuilding models have been formed in Indonesia, including in Tanjung Isui, East Kalimantan. While conflicts related to religion and culture have been increasing lately. Therefore, the study aims to investigate peacebuilding formation, including interreligious and intercultural processes in communities on Tanjung Isui. The analysis used in this study is ethnographic qualitative. The interreligious process that took place in Tanjung Isui Community occurred because religion forms local theological value system and becomes worldview of the community. The community mastered intercultural competencies such as appreciating other culture, adaptability, behavioral flexibility, strengthening interaction, identity management and interaction, awareness of differences, and cultural communication. While the elements building harmony in Tanjung Isui are the leadership spiritual role as mediator, wealth of values ​​and culture, then cooperation between religious and cultural followers.